ANALISIS TREND DAN DAMPAK PENGIRIMAN TKI: KASUS DUA DESA DI LOMBOK TIMUR, NUSA TENGGARA BARAT - Kurnia Novianti (Jurnal Kependudukan Indonesia, 2010)
Sending labor abroad is not a new phenomenon in Indonesia. Poverty and lack ofjobs, particularly in village areas, are the main reason why sending labor abroad is always happened each year. East Lombok, West Nusa Tenggara, is one of good examples. Thousand of peoples go abroad as workers in some of blue collar and domestic areas. Most of them are uneducated and have no skills. They come to Malaysia as plantation workers or to Saudi Arabia as servants. This field of works put them in a disadvantage position. As reported by the media, Indonesian workers are always the victims of their employer treatment, such as unpaid working, physically or sexually abuse, or over hours working. This article examines the trend and the impacts of sending workers abroad from two villages in East Lombok, West Nusa Tenggara. As the research results, people in these villages go to Malaysia and Saudi Arabia to get higher income, to earn money to build a house and to fulfill their family needs. But there are some social and cultural impacts of this process, such as stigma ofjamal (widow of a husband who went to Malaysia) and durab (widower of a wife who went to Saudi Arabia), and divorce rate. Based on this analysis, it is important for the Indonesian government to reconsider sending workers abroad is the only solution for the employment' problems.Keywords: Labor sending, trend, social and cultural impacts.